2023
DOI: 10.1001/jamanetworkopen.2023.40986
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Myopia Progression Interventions in Children

Sylvia Agyekum,
Poemen P. Chan,
Prince E. Adjei
et al.

Abstract: ImportanceSeveral interventions exist for treating myopia progression in children. While these interventions’ efficacy has been studied, their cost-effectiveness remains unknown and has not been compared.ObjectiveTo determine cost-effective options for controlling myopia progression in children.Design, Setting, and ParticipantsIn this cost-effectiveness analysis, a Markov model was designed to compare the cost-effectiveness of interventions for controlling myopia progression over 5 years from a societal perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Since the US Food and Drug Administration (FDA) and most regulatory authorities, with some few exceptions, have not granted regulatory approval for the use of any pharmacological agents for myopia control, in most countries, atropine is used off-label. Manufacturing atropine in low doses in bulk quantities would likely make it cost-effective [ 131 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the US Food and Drug Administration (FDA) and most regulatory authorities, with some few exceptions, have not granted regulatory approval for the use of any pharmacological agents for myopia control, in most countries, atropine is used off-label. Manufacturing atropine in low doses in bulk quantities would likely make it cost-effective [ 131 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the costs for optical interventions for myopia control are generally high, and thus only a small proportion of individuals globally will be able to access them. Agyekum et al compared the cost-effectiveness of various myopia interventions and estimated atropine 0.05% to reach an incremental cost-effectiveness ratio (ICER) of 220 USD per SER reduction [ 131 ]. In comparison, ICER for HALs was 448 USD per SER reduction and the that for OK lenses was 2376 USD/SER reduction.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis concluded that the use of 0.01% atropine is a cost-effective approach to managing myopia progression. Additionally, another analysis by Agyekum et al [ 41 ] compared 13 different interventions for controlling myopia progression in children, which included pharmacological agents, special contact lenses and spectacle lenses, using a Markov model. This economic evaluation suggested that atropine, particularly at a concentration of 0.05%, and outdoor activity are among the most cost-effective strategies for managing myopia progression.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the different survey methods and the 8 years between publications, the differences in parental attitudes between countries are profound 102,103 . Ophthalmologists sometimes make glib statements in publications regarding contact safety 104,105 that are not supported by the data presented above 95,96,99,100 . This may be driven by their own professional experience and seeing only the most serious cases of microbial keratitis.…”
Section: Summary and Other Considerationsmentioning
confidence: 99%